PENANGANAN PERMASALAHAN SAMPAH MELALUI SIMPAN MAGGOT (SOSIALISASI PEMILAHAN SAMPAH DAN PEMANFAATAN MAGGOT) - Pratama, Ruli Mulya; Sathiah N. A., Siti Faridah; Angelina, Calista; Shahla, Alzena Kevina; Sumartini, Yeni; Salsabila, Analisa; Khairunnisa, Natasya; Muharry, Andy (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Simpan Maggot: Socialization of Waste Sorting and Maggot Utilization in RW 09, Kahuripan Subdistrict, Tasikmalaya City. Organic waste is a major issue in RW 09, Kahuripan Subdistrict, Tasikmalaya City, requiring improved management to mitigate its enviromental impact. Black Soldier Fly (BSF) maggots offer an innovative solution for efficiently processing organic waste. This program aims to raise community awareness about waste sorting and organic waste management using maggots, fostering a healthier and more sustainable environment. Activities included education session, interactive discussions, and hands-on training. Evaluations were conducted through pre-test and post-test to assess participants’ knowledge improvement. The program enhanced community understanding of waste sorting and organic waste management using maggots. Active participation was observed during discussion and pratical sessions. Simpan Maggot successfully raised community awarness about sustainable waste management. This program can serve as a model for other areas to support clean and healthy enviroments.